Franquias sociais: minimizando riscos no investimento social - Rota, Sergio Luiz (2004)
Over the last few years there has been a growing interest in social responsibility, both as concept and practice, as social problems emerge and as expectations increase as to contribute that the organizations can make as qualified. From this perspective, the business sector has been facing pressures originating from consumer defense movements, campaigns to combat extreme poverty and famine, as well as others that appear as a result of the exacerbation of issues related to minorities excluded from social life. In an attempt to respond to such demands, companies are incorporating a social commitment to their business objectives as market differentiation and highly relevant social benefits for the improvement of situations which it is applied. This study focus on the issue of social responsibility in business and the alternative of franchising methodology, or social franchising, for social actions for companies of Ceará state. The approach of the investigation is predominantly qualitative and starts out from a bibliographic review of the topics at issue seeking to comprehend their interactions and incorporations into business practices, with a view to applying using the social franchising. In the universe of 32 companies that have to participate in the contest 'Premio Delmiro Gouveia' of the best companies of Ceará state. The sample corresponds to 22 of these organizations where the informations were available. The found results show that's the methodology of the social franchising has a positive view of the business people and new studies about the subject will be led to ,make the theoretical reference more wide-raging that is now available.